The Effect of Project Based Learning Assisted by Mobile Learning Applications and Learning Motivation on the Competence and Performance of Teachers (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
One learning model that can be used to improve teachers' quality, pedagogic competence, and personality is the Project Based Learning (PjBL) learning model. The development in research carried out the Project Based Learning (PjBL) learning model in collaboration with applying the mobile learning model. The use of project-based learning using mobile applications focuses on optimizing teacher performance. The results of this study are: (1) There is an influence of the PjBL strategy assisted by the Mobile Learning Application on the pedagogical competence of teachers. It shows by the significant p-value